Shrimp aquaculture in Mexico. - Miller, Margaret (1990)
Investigates the interplay of economic, legal and institutional considerations that have stood in the way of greater Mexican participation in the aquaculture revolution, and the dilemmas posed by policy reforms that will need to be resolved if a more dynamic industry is to emerge. Suggests that, in part, the problems that have been encountered have arisen because of the institutional fragmentation created by successive legislative acts designed to deal with the difficulties of the traditional high-seas and estuary fisheries.